richobezoar as a cause of upper intestinal obstruction (Colombia Medica, 1994)
This paper presents the case of a 12-year-old girl with a diagnosis of tri cho bezoar, treated surgically, with positive evolution. Trichobezoars are very unusual foreign bodies composed of hair and food particles that form a case inside the stomach or bowel, causing intestinal obstruction. There is little literature reported on this disorder. The pathology is reviewed, and guidelines are given for its treatment